Programming ASP.NET MVC 4 - Chadwick, Jess (O'Reilly Media, 2012)
Get up and running with ASP.NET MVC 4, and learn how to build modern server-side web applications. This guide helps you understand how the framework performs, and shows you how to use various features to solve many real-world development scenarios you're likely to face. In the process, you'll learn how to work with HTML, JavaScript, the Entity Framework, and other web technologies. You'll start by learning core concepts such as the Model-View-Controller architectural pattern, and then work your way toward advanced topics. The authors demonstrate ASP.NET MVC 4 best practices and techniques by building a sample online auction site ("EBuy") throughout the book. Learn the similarities between ASP.NET MVC 4 and Web Forms Use Entity Framework to create and maintain an application database Create rich web applications, using jQuery for client-side development Incorporate AJAX techniques into your web applications Learn how to create and expose ASP.NET Web API services Deliver a rich and consistent experience for mobile devices Apply techniques for error handling, automated testing, and build automation Use various options to deploy your ASP.NET MVC 4 application.